Whole-catchment inventories of trace metals in soils and sediments in mountain lake catchments in the Central Pyrenees: apportioning the anthropogenic and natural contributions - Bacardit, Montserrat; Krachler, Michael; Camarero, Lluís (Geochimica et cosmochimica acta, 2012)
We measured the concentrations of Pb, Zn, Cd, Cu and Ni in rocks, soils, sediments and plants from three catchments in the Central Pyrenees, with the aim of producing whole-catchment inventories for these trace metals and apportioning natural and anthropogenic fractions. We used Pb isotopes to distinguish between natural and contaminant Pb, and compared the results to apportioning based on reference element ratios (e.g. Pb/Ti) in order to validate this second method. Both methods gave similar results, except in one of the catchments where soils presented a highly organic upper horizon with a different geochemistry. Because of this, specific element ratios had to be used for the organic horizon that were different from those used for the mineral horizon, in order to obtain the correct apportioning as estimated by the Pb isotope method. Taking this into account, we then calculated inventories for the other metals for which isotopic methods are not available. Previous studies have shown that Pb contamination started in the area as early as the 1st century BCE. In the present study, the earliest indication of Pb contamination in lake sediments was dated ∼1250 CE and has continued until the present. During the 19th century, there was a change in the source of anthropogenic Pb as indicated by its isotopic composition. The estimated inventories of anthropogenic trace metals for the whole catchments were ∼1gm−2 of Pb and Zn, ∼0.1-0.2gm−2 of Ni and Cu and ∼0.01gm−2 of Cd. The Pb and Zn inventories are similar to those for other mountainous and rural areas in northern and eastern European locations, whereas Ni, Cu and Cd inventories were lower in the Pyrenees. The anthropogenic trace metals accumulated in Pyrenean catchments were three orders of magnitude higher than the current yearly atmospheric deposition over the area. This indicates the potential of sediments and soils as sources of a delayed contamination caused by the remobilisation of anthropogenic trace metals accumulated over the course of time.
Received 31 December 2009, Accepted 16 October 2010, Available online 1 March 2012
Gesehen am 09.05.2018